2019
DOI: 10.1111/febs.15176
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic promiscuity and the evolution of bioluminescence

Abstract: Bioluminescence occurs when an enzyme, known as a luciferase, oxidizes a small‐molecule substrate, known as a luciferin. Nature has evolved multiple distinct luciferases and luciferins independently, all of which accomplish the impressive feat of light emission. One of the best‐known examples of bioluminescence is exhibited by fireflies, a class of beetles that use d‐luciferin as their substrate. The evolution of bioluminescence in beetles is thought to have emerged from ancestral fatty acyl‐CoA synthetase (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 76 publications
(133 reference statements)
0
23
0
Order By: Relevance
“…Coincidental, promiscuous activities serve as a starting point and, via mutation and selection, these gradually become the native, physiological function of the new enzyme. Stephen Miller and Spencer Adams [2] describe a specific case of duplication and divergence of a fatty acyl‐CoA synthetase that led to insect luciferases that were repurposed to generate light by oxidizing luciferin. Margaret Glasner and co‐authors [3] address another main source of new enzymes – horizontal gene transfer – and how, in combination with promiscuity, this enables the evolution of new metabolic pathways.…”
mentioning
confidence: 99%
“…Coincidental, promiscuous activities serve as a starting point and, via mutation and selection, these gradually become the native, physiological function of the new enzyme. Stephen Miller and Spencer Adams [2] describe a specific case of duplication and divergence of a fatty acyl‐CoA synthetase that led to insect luciferases that were repurposed to generate light by oxidizing luciferin. Margaret Glasner and co‐authors [3] address another main source of new enzymes – horizontal gene transfer – and how, in combination with promiscuity, this enables the evolution of new metabolic pathways.…”
mentioning
confidence: 99%
“…When we considered hAGP as a luciferase to be used for a reporter assay or in vivo imaging, the luminescence intensity from the combination of hAGP with Cypridina luciferin was much lower than that from known luciferin-luciferase systems ( Table 1 ). However, because molecular evolutionary studies have reported better bioluminescence systems using a non-natural luciferase or a synthetic luciferin analog [ 41 , 42 , 43 ], molecular engineering of hAGP or synthetic improvement of Cypridina luciferin could produce a practical Cypridina luciferin-based hAGP detection system to observe biological processes. Possibly, since known luciferases do not originate from mammalian proteins, the hAGP-based system could allow us to observe an intact biological event in mammalian systems.…”
Section: Discussionmentioning
confidence: 99%
“…Acyl-CoA synthetic activities of ancestral firefly luciferases Firefly luciferases are bifunctional enzymes; in addition to luciferase (luminescence) activity, they have a "promiscuous" acyl-CoA synthetic (ACS) activity to various fatty acids ( Fig. 1A) (13)(14)(15). Consequently, it has been hypothesized that the firefly luciferases originated from a fatty acyl-CoA synthetase (15).…”
Section: Downloaded Frommentioning
confidence: 99%
“…1A) (13)(14)(15). Consequently, it has been hypothesized that the firefly luciferases originated from a fatty acyl-CoA synthetase (15). We examined ACS activities of the seven ancestral luciferases using lauric acid as a substrate.…”
Section: Downloaded Frommentioning
confidence: 99%